1990
DOI: 10.1099/00221287-136-12-2555
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of insertion sequence IS200 in Salmonella and Shigella

Abstract: Two DNA probes for the detection of insertion sequence IS200 by either Southern blotting or colony hybridization were constructed. One of the probes is a 300 bp EcoRI-Hind111 fragment of IS200 cloned onto pBluescript KS( +); the other is a tail-to-tail dimer of the same fragment cloned onto pUC19. A survey of the presence of IS200 among enteric bacteria revealed that more than 90% of the pathogenic or food-poisoning isolates of Salmonella spp. examined contained one or more copies of insertion sequence IS200, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 18 publications
3
73
2
Order By: Relevance
“…Like the strains of S. enteritidis PT 24 described above, these strains of S. enteritidis PT 23 were also found to possess an Inc N plasmid of 34 MDa which coded for resistance to ampicillin and streptomycin, but not to tetracyclines [6].…”
Section: Drug Resistance Typingmentioning
confidence: 82%
See 1 more Smart Citation
“…Like the strains of S. enteritidis PT 24 described above, these strains of S. enteritidis PT 23 were also found to possess an Inc N plasmid of 34 MDa which coded for resistance to ampicillin and streptomycin, but not to tetracyclines [6].…”
Section: Drug Resistance Typingmentioning
confidence: 82%
“…IS200 is a salmonella-specific insertion element first described by Lam and Roth [33] and distributed on conserved loci on the chromosome of many salmonella serotypes [34]. Certain characteristics of IS200 favour its use as a probe for strain discrimination and using IS200, three 'clonal lineages', designated SEClI, SEClII and SEClIII have been identified within the chromosomes of 27 of the S. enteritidis phage type strains [35].…”
Section: Is200 Typingmentioning
confidence: 99%
“…Significantly increased expression occurred most frequently for transposases from the family IS200/IS605, suggesting not only that nutrient limitation may regulate transposase gene expression, but that it specifically targets expression of a single family. This family of transposases is also widespread in the genomes of multiple pathogenic bacteria (Gibert et al, 1990): similar behavior of these elements among pathogens and proteomic identification of transposases in endosymbionts and an acid mine drainage community may have ramifications for the ability of such organisms to infect a host or adapt to an environment (Chao et al, 1983;Ram et al, 2005;Kleiner et al, 2013). Homologs of the IS200/605 family have been identified across both eukaryotes and eukaryote-infecting viruses, suggesting these results may have implications in all domains of life (Bao and Jurka, 2013).…”
Section: Genomic Consequences Of Nutrient Conditionsmentioning
confidence: 99%
“…The enzyme used from the previously reported sporadic cases, allowing one to detect the peculiarity of the outbreak isolate. was PstI which does not cut within IS200 and provided the clear resolution (Gibert et al 1990). PstI analysis showed Each method used in this study was found to be efficient as an epidemiological marker; because of the rarity of isolation different profiles of IS200 insertion in Salm.…”
Section: Resultsmentioning
confidence: 99%
“…Agarose (Bio-Rad, Hercules, CA) for gel electrophoresis was used at Outbreak a concentration of 0·8%. Plasmid pIZ46 (kindly provided by Dr José Casadesùs, In September 1994 out of 2206 people, workers and waiters, having consumed lunch in a factory canteen in Montalto di University of Seville, Spain) containing a tail-to-tail dimer of the EcoRI-HindIII fragment of IS200 (Gibert et al 1990) was Castro (Viterbo), 437 developed gastroenteritis. Out of the Salmonella sp.…”
Section: Division Of Enteric Pathogens Public Health Laboratorymentioning
confidence: 99%